The COVID-19 Diaries: Identity, Teaching, and Learning at a Crossroads - Sequeira, Lavina; Dacey, Charity M. (Frontiers in Education, 2020)
Despite the fact that American education has at its core strived to provide pathways of opportunity to remedy socio-economic inequalities, as educational institutions transitioned into online virtual classrooms due to the COVID-19 pandemic these inequalities have come into sharper focus for us. During the process of engaging in a larger self-study, we became more aware of the stark socio-economic disparities of our students in a virtual space, specifically amongst students of color and how these disparities affected learning outcomes and their identity. Juxta positioning the situated in-between spaces of in-class and virtual environments our identities as educators were fluid and intersectional, negotiated in response to student interactions thereby enabling changes in our Dialogical Selves. The sample for this study consisted of 2 faculty members and 40 students. Data sources included reflexive journals, recorded class sessions, students’ questionnaires, and artifacts such as student feedback collected through “exit tickets” as well as recorded meetings. Some findings include 1) students’ identities were negotiated differently in face to face classrooms versus virtual classrooms, 2) fluidity in intersectional identity due to intersections of I-positions in the dialogical self and 3) acknowledging and accepting the presence of COVID-19 created a sense of community in the virtual classroom 4) incorporating self-care and caring pedagogical practices provided a empowering space for students and educators.